Samahang Nayon officer's responsibility to management training - Naldoza, Arnold M. (University of the Philippines at Los Baños, 1979)
The study sought to determine the socioeconomic profile of Samahang Nayon officers and the relationship between symbolic and use adoption regarding the management lessons. Anent socioeconomic characteristics, the members were older by three years; more officers had higher educational attainment; both had equal number of dependents; more members were engaged in farming; and more officers were more secure in tenure. A slight difference was observed between them regarding farm size and rice production per hectare. On the use adoption of the savings obligations, both had low performance. The number of weeks and sessions of training as prescribed by the manual was not observed in practice. Seventy-one percent of the officers as against 28 percent of the members attended all lessons. The officers exhibited higher symbolic adoption rating. When asked about their competence to assume leadership position after the management training, the officer claimed their preparedness while the members expressed their uncertainty. Educational attainment was inversely related to symbolic adoption while training experience was directly associated. Inversely related to use adoption of barangay guarantee fund were age, educational attainment, tenure, training experience and frequency of MDO visits, except major occupation which was directly associated. Directly related to use adoption of barangay savings fund were educational attainment and frequency of MDO/BDW visits. Symbolic adoption and use adoption were not significantly related regarding the functions of officers; however, they were found to be inversely associated regarding the savings obligations.